1999
DOI: 10.1212/wnl.53.7.1425
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D 2 receptor gene polymorphism and the risk of levodopa-induced dyskinesias in PD

Abstract: Certain alleles of the short tandem repeat polymorphism of the dopamine receptor D2 gene reduce the risk of developing peak-dose dyskinesias and could contribute to varying susceptibility to develop peak-dose dyskinesias during levodopa therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(71 citation statements)
references
References 36 publications
1
65
2
Order By: Relevance
“…Female gender, earlier age at onset of PD and a longer duration of levodopa therapy have been associated with a higher risk of developing peakdose dyskinesias [49]. Genetic factors could also contribute to individual variability in the development of peak-dose dyskinesias.…”
Section: Polymorphisms Associated With Drug Tolerancementioning
confidence: 99%
“…Female gender, earlier age at onset of PD and a longer duration of levodopa therapy have been associated with a higher risk of developing peakdose dyskinesias [49]. Genetic factors could also contribute to individual variability in the development of peak-dose dyskinesias.…”
Section: Polymorphisms Associated With Drug Tolerancementioning
confidence: 99%
“…Interestingly, both studies found that the DRD2 gene was involved in the development of different types of motor complications, namely, wearing off and PDD. These results suggest that the DRD2 gene might play a pivotal role 20,189 in the genetic susceptibility to the motor complications induced by levodopa in PD, but this should be further examined.…”
Section: Pharmacodynamics: Dopamine Receptorsmentioning
confidence: 93%
“…nor was there an association of smoking and PD risk with the presence of these polymorphisms. The remaining four studies examined the polymorphic dinucleotide repeat in the second intron of the DRD2 gene, [17][18][19][20] but only two of them 18,20 found a significant association between this polymorphism and PD in Caucasians.…”
Section: Genetic Variations With Potential Effect On Pd Risk: Dopaminmentioning
confidence: 99%
See 2 more Smart Citations